1981
DOI: 10.1002/mpo.2950090204
|View full text |Cite
|
Sign up to set email alerts
|

Religion in patients with advanced cancer

Abstract: Data on religious belief, activity, and connections, and ratings of happiness, life satisfaction, and pain level were obtained periodically from 71 patients with advanced cancer. Religious belief showed substantial positive correlation with life satisfaction, and religious activity and connections were significantly correlated with both happiness and life satisfaction. Religious patients also reported significantly lower levels of pain, even though they were no less likely to report the presence of pain. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(113 citation statements)
references
References 6 publications
2
107
0
4
Order By: Relevance
“…37,38 Thus, coping occurs both among the well and the ill. Coping can complement rational problem-solving but is not necessarily identical with it because it draws upon emotional, social, and other resources that are not strictly limited to cognitive resources. Religious and spiritual resources have been shown to be helpful for managing pain 39,40 and improving life satisfaction during illness, including terminal illnesses like advanced cancer. 34,41 Religious coping strategies occur in positive and negative varieties.…”
Section: Religious Coping With Disease and Disabilitymentioning
confidence: 99%
“…37,38 Thus, coping occurs both among the well and the ill. Coping can complement rational problem-solving but is not necessarily identical with it because it draws upon emotional, social, and other resources that are not strictly limited to cognitive resources. Religious and spiritual resources have been shown to be helpful for managing pain 39,40 and improving life satisfaction during illness, including terminal illnesses like advanced cancer. 34,41 Religious coping strategies occur in positive and negative varieties.…”
Section: Religious Coping With Disease and Disabilitymentioning
confidence: 99%
“…Thus, in patients with advanced cancer, there is a significant correlation between religious faith and and 10 women (mean age 66 years, range 46-84) who had not received post-operative chemotherapy; 17 had acceptance of the situation, and lower levels of pain in those who have religious belief [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study differs from earlier reported studies in the sense that most of those studies have been done in patients who were suffering from incurable chronic diseases and therefore were already in poor health. (22,23,24) Such population displays a lot of psychological component responsible for their wellbeing besides actual benefits from any intervention. Our study subjects included healthy medical students who were already, at least apparently, enjoyed good physical and mental health and had an above average IQ.…”
Section: Resultsmentioning
confidence: 99%